Join Sarthaks eConnect Today - Largest Online Education Community!
0 votes
4 views
in Sets, Relations and Functions by (51.9k points)
closed by

If f(x) = (4x + 3)/ (6x – 4), x ≠ 2/3, show that (f o f) (x) = x for all x ≠ 2/3. Hence, find f -1.

1 Answer

+1 vote
by (24.5k points)
selected by
 
Best answer

It is given that

f(x) = (4x + 3)/ (6x – 4)

Here we know that

fof = fof (x) = fo{f(x)} = f{(4x + 3)/ (6x – 4)}

By substituting the values we get

Therefore, fof (x) = x and fof = 1

So f -1 = 1 where f -1 = (4y +3)/ (6y – 4)

Related questions

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...